Pengembangan sosialisasi produk bank syariah indonesia (produk pensiun dan pra pensiun BSI KCP Cirebon plered 2) - sekarsari; Lukmanul Hakim; Achmad Nurjannah (Al Naqdu, 2020)
The purpose of this study is to find out how the development of socialization in promoting products from Indonesian Islamic banks. This research use desciptive qualitative approach. The data obtained in this article were obtained through observation, interviews and documentation techniques with customers related to research problems. The results of the study found advantages and disadvantages in carrying out promotions through direct socialization with customers. By doing this, customers can find out what products are available in Indonesian Islamic banks without having to go to the bank, the weakness is that many customers are hesitant to buy. take products from Indonesian Islamic banks because of the limited knowledge of customers about the differences between Islamic banks and conventional banks.